Twisted fate : a novel - Olson, Norah (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2015)
Told from separate viewpoints, unfolds how sisters Sydney and Ally Tate's relationship changes as they get involved with their new neighbor, Graham, an artist with a videocamera who has a mysterious--and dangerous--past.